THE ASSOCIATION OF CARBOHYDRATE AND PROTEIN INTAKE WITH THE INCIDENCE OF WASTING IN TODDLERS - Herdiani, Novera; Sari, Aqilia Shofi Kurnia (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
One of the most significant nutritional health problems in children is wasting. Inadequate carbohydrate and protein intake in toddlers is a leading cause of wasting. This study aimed to analyze the relationship between carbohydrate and protein intake and the incidence of wasting in the working area of the Driyorejo Gresik Health Center. The study employed a quantitative observational analytic cross-sectional approach. The sample consisted of 107 mothers with toddlers aged 12–59 months. Data were collected using questionnaires and 2x24-hour food recall. Multistage cluster random sampling was used for sample selection, and data were analyzed using the chi-square test. The results showed that nearly all toddlers (78.5%) had deficient carbohydrate intake, while most (69.2%) had deficient protein intake. Additionally, the majority of toddlers (81.3%) experienced wasting. The chi-square test revealed a significant relationship between carbohydrate and protein intake and the incidence of wasting (p-value = 0.000, <0.05). In conclusion, there is a significant association between inadequate carbohydrate and protein intake and wasting among toddlers in the Driyorejo Gresik Health Center area. To reduce the risk of wasting, mothers and caregivers are encouraged to ensure balanced nutrition, meeting the required carbohydrate and protein intake for toddlers.